Pengaruh Return on Asset, Debt to Equity Ratio, dan Current Ratio Terhadap Return Saham - Angrawit Kusumawardani (Forum Kerjasama Pendidikan Tinggi, 2023)
Stock return is the result obtained from the investment made by investors. Stock returns are influenced by various factors including Return on Assets, Debt to Equity Ratio, and Current Ratio. This study aims to determine the effect of Return on Assets, Debt to Equity Ratio, and Current Ratio on Stock Returns in pharmaceutical sub-sector companies listed on the IDX in 2016-2020 both simultaneously and partially. The sampling method in this study was purposive sampling of 7 pharmaceutical companies listed on the Indonesia Stock Exchange from 2016 to 2020. The data used is secondary data. The analytical method used was multiple linear regression analysis with the SPSS version 25 application tool. The results of the t (partial) test showed that the Return on Assets and Debt to Equity Ratio variables obtained significant values ??of 0.940 and 0.446 which indicated that the Return on Assets and The Debt to Equity Ratio has no effect on Stock Return partially because the significant value is > 0.05. While the Current Ratio variable obtained a significant value of 0.007 which indicates that the Current Ratio variable has a partial effect on stock returns because the significant value is <0.05. Based on the results of the F test in table 4.9 it is known that the significant probability value is 0.043 which indicates that the probability value is significant <0.05. Meanwhile, the results obtained by the F-count were 3.061 > from the F-table, which was 2.90. So it can be concluded that this shows that the variables Return On Assets, Debt to Equity Ratio, and Current Ratio have a simultaneous influence on Stock Returns.